Reconstruction of financial sustainable growth rate model for SMEs - Lin, Zhongshu; Lau, Yeng Wai; Mohammed Shah, Sabarina; Shi, Ruichuan; Cao, Qinglou; Tan, Yuan (Cogent OA, 2026)
Small and medium-sized enterprises (SMEs) face unique growth challenges not captured by traditional financial sustainable growth rate (SGR) models. This study examines how SMEs construct a tailored SGR model amid dynamic development by leveraging sustainable financial mechanisms. Conceptually, drawing on literature pertaining to enterprise growth, development, and maturity, this study clarifies the definition of SME sustainable growth, resolving the ambiguity in this concept that has long persisted as a research gap. Methodologically, this study develops an adjusted SGR model that addresses the limitations of the Higgins and Van Horne models, as their static nature conflicts with the dynamic operational contexts of SMEs. Using 2012–2021 panel data from China’s Growth Enterprise Market, this study compares four models via OLS regression, prediction metrics, and information criteria. The adjusted model, incorporating operating and financial leverage, exhibits superior explanatory power, smaller prediction errors, and better simplicity. Traditional models assume zero leverage and fixed costs, misaligning with SME realities, while the adjusted model captures growth constraints through cost structure and leverage dynamics. This framework helps SMEs balance growth and risk, advocating dynamic over static modeling for SME-specific growth analysis.